2022
DOI: 10.1371/journal.pone.0277730
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the impact of financial inclusion on economic growth: A global perspective

Abstract: Financial inclusion is critical to inclusive growth, proffering policy solutions to eradicate the barriers that exclude individuals from financial markets. This study explores the effects of financial inclusion on economic growth in a global perspective with a large number of panels classified by income and regional levels from 2002–2020. The analysis begins with the development of a comprehensive composite financial inclusion index comprised of penetration, availability, and usage of financial services and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…Despite the disadvantages, financial inclusion still contributes positively to economic growth in the long run. Our empirical result regarding the role of financial inclusions in short run and long run can be supported by several empirical studies (Dai et al, 2022;Huang et al, 2021;Ifediora et al, 2022;Jima, 2023;Menyelim et al, 2021;Azimi, 2022;Obayori & George-anokwuru, 2020) conducted by taking overall relationship of financial inclusion and economic growth in difference aspect.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Despite the disadvantages, financial inclusion still contributes positively to economic growth in the long run. Our empirical result regarding the role of financial inclusions in short run and long run can be supported by several empirical studies (Dai et al, 2022;Huang et al, 2021;Ifediora et al, 2022;Jima, 2023;Menyelim et al, 2021;Azimi, 2022;Obayori & George-anokwuru, 2020) conducted by taking overall relationship of financial inclusion and economic growth in difference aspect.…”
Section: Discussionsupporting
confidence: 72%
“…At the core of this effort is the concept of financial inclusion -a comprehensive approach that aims to provide equitable and unrestricted access to financial services for all society's consumers, especially those demoted and lacking access to traditional banking services. As a result, the relationship between financial inclusion and economic growth has gained significant attention and has been subject to extensive empirical research (Chen et al, 2023;Ifediora et al, 2022;Jima & Makoni, 2023;Menyelim et al, 2021;Azimi, 2022;Nwisienyi & Obi, 2020;Emara & El Said, 2021;Ozili, 2020). Countries increasingly recognise the importance of inclusive financial systems in driving economic development and reducing social and economic inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated a significant association between financial inclusion and economic growth (Uzoma et al, 2022;Sethi & Acharya, 2018;Ratnawati, 2020;Azimi, 2022). Financial inclusion has been identified as a driver of economic growth in various countries, including Nigeria (Uzoma et al, 2022).…”
Section: Relationship Between Financial Inclusion and Economic Empowe...mentioning
confidence: 99%
“…These cooperatives have the power to generate employment, reduce poverty and enable social engagement for overall empowerment (Lal, 2019). Various researchers strongly argue that financial participation not only eradicates poverty but also influences economic prosperity (Azimi, 2022;Khan, Haouas, Trinh, Badeeb, & Zhang, 2023;Omar & Inaba, 2020). Similarly, studies also argue that financial participation through cooperative efforts improves inclusive finance, reduces poverty, creates employment and improves the quality of life, all of which lead to socio-economic development and social integration.…”
Section: Socio-economic Empowerment Through Financial Participationmentioning
confidence: 99%